Odpowiedzi

2009-12-09T19:06:24+01:00
4a-2=b
3a+7b=1,5

b=4a-2
3a+7(4a-2)=1,5

b=4a-2
3a+28a-14=1,5

b=4a-2
31a=15,5

a=0,5
b=4*0,5-2=2-2=0
2009-12-09T19:12:54+01:00
4a-2=b
3a=1,5-7b : 3

4a-2=b
a = 0,5 - 2⅓b

4(0,5- 2 ⅓b) -2 = b
a= 0,5 - 2⅓b

-8⅓ = b
a= 0,5 - 2⅓b

b= -8⅓
a= 0,5 - 2⅓(-8⅓)

b = 8⅓
a= 0,5 + 16 i jedna dziewiąta

b= 8 ⅓
a= 16 ⅚
2009-12-09T19:17:19+01:00
4a-2=b
3a+7b=1,5

3a+7(4a-2)=1,5
3a+28a-14=1,5 /+14
31a=12,5
a=0,5
b=4*(0,5)-2=0
spr.
4a-2=b
4*(0,5)-2=0
L=P
3a+7b=1,5
3*(0,5)+7*0=1,5
1,5=1,5
L=P